On occupants and owners. Conflicts among neighbors in the Buenos Aires frontier. Chascomús and Ranchos, 1800-1840 (Quinto Sol, 2013)
In this paper, conflicts among neighbors since the last days of the colonial period up to the end of the use of enfiteusis in the 1840 are studied, when de facto posession  over a plot was on the way to become full property, whenever title deeds could be got by means of different  sistems for the awarding of public fields. Attention is focused on territory occupation and rights acquired in Chascomús and Ranchos districts. From the analysis of lawsuits, the hacendados [cattle-dealers] plays of interests can be appreciated, as well as their conections with the civil power in the frontier, that are defined in the extra-judicial solution of the conflict. Besides, the role of authorities and the judgment’s grounds and examined. We examine the reasons for the conflicts and the arguments posed the partes, which, as a whole, shed light as regards the use of legislation and the permanency of consuetudinary norms. It is therefore demonstrated how the old possesion was everytime more compromised as a precarious judicial figure, as new laws, and decrees were conditioning the awarding of title deeds to public lands, especially those related with the enfiteusis, though it held a great importance, during the whole period.
Keywords: Occupation; legal property; conflicts; old settlement